Nursing clinical practice guidelines to improve care for people undergoing percutaneous coronary interventions - Rolley, J.; Salamonson, Y.; Wensley, C.; Dennison, C.; Davidson, Patricia (Elsevier Inc, 2010)
Aim: The aim of this paper is to present a set of nursing clinical practice guidelines for individuals undergoing percutaneous coronary interventions (PCIs) together with a summary of the evidence to support these recommendations. Background: Percutaneous coronary intervention is a common procedure requiring expert nursing care delivered within an interdisciplinary team. Although evidence-based medical practice guidelines exist, they include minimal information to guide nursing-specific care. Guidelines development: The guidelines development process used a framework of the patient journey. Three steps leading up to this paper were undertaken: (1) a comprehensive literature review; (2) a consensus development workshop; and (3) a modified Delphi technique to refine the guideline recommendations. Summary: Clinical practice guidelines to support interventional cardiology nursing care are limited. This paper represents an important contribution toward meeting this need. Implications for practice: These guidelines, developed within a context of Australian and New Zealand nursing practice, provide an important foundation to enable benchmarking and ongoing developing clinical practice standards.